2010
DOI: 10.1186/1471-2334-10-145
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with death in hospitalized pneumonia patients with 2009 H1N1 influenza in Shenyang, China

Abstract: BackgroundDuring the spring of 2009, a pandemic influenza A (H1N1) virus emerged and spread globally. We describe the clinical characteristics and factors associated with the death of patients who were hospitalized with 2009 H1N1 influenza pneumonia in Shenyang, China, from November to December 2009.MethodsWe carried out a retrospective chart review of 68 patients who were hospitalized with pneumonia and confirmed to have 2009 H1N1 virus infection by a real time RT-PCR assay of respiratory specimens.ResultsOf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
91
8
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(125 citation statements)
references
References 24 publications
22
91
8
4
Order By: Relevance
“…Our results confirm previous reports indicating that young and middle-aged individuals infected with pH1N1 are more prone to develop severe complications, as opposed to patients with seasonal influenza where the elderly was the most affected group [9,24]. In the areas of southern China covered in this study, human Infection with pH1N1 virus culminated in 50% of ILI cases with higher rates of hospitalization (39%) and recovery (100%) compared with other cohorts from the United States, Mexico, Canada, and Beijing [3,10,25,26], illustrating a slightly different trend of pandemic infection in this region.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results confirm previous reports indicating that young and middle-aged individuals infected with pH1N1 are more prone to develop severe complications, as opposed to patients with seasonal influenza where the elderly was the most affected group [9,24]. In the areas of southern China covered in this study, human Infection with pH1N1 virus culminated in 50% of ILI cases with higher rates of hospitalization (39%) and recovery (100%) compared with other cohorts from the United States, Mexico, Canada, and Beijing [3,10,25,26], illustrating a slightly different trend of pandemic infection in this region.…”
Section: Discussionsupporting
confidence: 82%
“…According to the Chinese Ministry of Health, approximately 197,000 suspected cases of influenzalike illness (ILI) were observed during the 2009-2010 flu season (http://www.cnic.org.cn/eng) with a considerably high proportion of hospitalizations, ICU admissions, and deaths [5][6][7][8]. However, available data, mostly based on case reports and retrospective analyses, portray the clinical picture of cases as situated in urban areas of the country, especially in Beijing and Shanghai, which are more likely to have been affected by international travel and do not represent a large portion of the Chinese population [4,[6][7][8][9][10][11][12]. Southern parts of mainland China, where Shantou and Nanchang are located, represent smaller urban centers more than the typical Chinese demographics.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of lethality varies among published studies and it ranges from 10% to extreme 59%, which certainly depends on the various conditions and criteria according to which the patients are analyzed as well as on the criteria for admission to intensive care units [13][14][15]. Thus, the study performed in China showed that from 60 patients with severe form of influenza 44% were treated at Intensive care unit and the lethality was 14.7% [16].…”
Section: Discussionmentioning
confidence: 99%
“…During the period of our study, the pandemic strain of community acquired pneumonia resulted in the death of 16.34% patients in the sample. Some of previous study had found approximate result, for example, 18.79% in [12] 14.7% in Cui et al [14], 23.8% in Kuo-Tung [25].…”
Section: Discussionmentioning
confidence: 87%
“…Variables considered at individual/patient level in the study were selected based on some previous study [9,[12][13][14][15][16] and those that are expected to be the factors/determinants of mortality of under-five from hospitalized patients of CAP. Number of nurse on service in a given month * Length of Hospital stay is the number of colander days from the days of patient admission to the day of discharge…”
Section: Variables Considered In the Studymentioning
confidence: 99%